Comparative studies of the Malay and Malay-Muslim traditional house as architectural heritage built forms - Abdul Majid, Noor Hanita; Mohd Nawawi, Norwina (IIUM Press, 2011)
The similarities found in the architectural styles of the Malay and Malay-Muslim traditional houses as architectural heritage built form in the Southeast Asian region have triggered many theories among architectural writers and critics of it origin. This article intends to discuss selected theories and review some examples of architectural forms found in Thailand, Indonesia, Malaysia, Cambodia, Laos PDR and Vietnam as bases of understanding the development ofthe civilization that is profoundly connected to the architectural establishment in both styles and typologies. Qualitative approach through literature review and observational visits to case studies in the region was adopted for this study. The preliminary findings suggest the pragmatism of approach in the similarities and differences of the architectural forms explains implicitly the origins ofthe Malay architectural heritage.